A Pilot Study on Gait Kinematics of Old Women with Bound Feet - Yan Zhang; Neng Feng; Nanzhi Hu; Yaodong Gu (Applied Bionics and Biomechanics)
Foot binding has a long and influential history in China. Little is known about biomechanical changes in gait caused by bound foot. The purpose of this study was to investigate the differences in lower limb kinematics between old women with bound feet and normal feet during walking. Six old women subjects (three with bound feet and three controls with normal feet) volunteered to participate in this study. Video data were recorded with a high speed video camera and analysed in the SIMI motion analysis software. Compared to normal controls, bound feet subjects had faster gait cadence with shorter stride length as well as smaller ankle and knee range of motion (ROM). During preswing phase, ankle remained to be dorsiflexion for bound foot subjects. The data from bound foot group also demonstrated that toe vertical displacement increased continuously during whole swing phase without a minimum toe clearance (MTC). The findings indicate that older women with bound feet exhibit significant differences in gait pattern compared to those with normal feet, which is characterised by disappeared propulsion/push-off and reduced mobility of lower limb segments.